A BiOBr/Co–Ni layered double hydroxide nanocomposite with excellent adsorption and photocatalytic properties. Issue 67 (24th July 2015) - Ao, Yanhui; Wang, Dandan; Wang, Peifang; Wang, Chao; Hou, Jun; Qian, Jin
<x xml:space="preserve">Abstract</x> A novel BiOBr/Co–Ni–NO3 layered double hydroxides (LDHs) nanocomposites were prepared by an in situ growth method. The as-prepared samples showed much higher adsorption and photocatalytic properties on organic dyes phenol.